Penerapan Strategi Bertahan Hidup Terhadap Tekanan Ekonomi Pengrajin Gerabah Desa Purwoasri Pacitan - Fina Nasikhatul Ula; Choirul Daroji (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo, 2024)
The people of Purwoasri Pacitan Village use pottery as a livelihood to meet their daily needs. The pottery artisans continue to survive even though their income from selling pottery is insufficient to meet their living needs. This research analyzes pottery artisans' active, passive, and network strategies in Purwoasri Village, Kebonagung Pacitan District. This research uses qualitative research methods, and type research is field research, and data obtained through interviews, observation, and documentation; the analysis method in this research is phenomenology, namely by analyzing the survival strategies experienced by pottery artisans in Purwoasri Village, Kebonagung District, Pacitan. The results of this research are (1) Active strategies experienced by families of pottery craftsmen, namely looking for side jobs by becoming construction workers, agricultural laborers, farmers and casual workers. (2) The passive strategy experienced by pottery artisans is to adopt a culture of frugal living. If they make much profit or their economic conditions are good, they go to the health center with KIS or BPJS, and buy medicine at the pharmacy when they are sick. (3) The network strategy experienced by pottery artisans generally borrows money from relatives, neighbors, and cooperatives, and some also borrow money from banks.